Environmental instability reduces shock resistance by enriching specialist taxa with distinct two component regulatory systems - Simon Mills; Umer Zeeshan Ijaz; Piet N. L. Lens (npj Biofilms and Microbiomes)
Abstract Different microbial communities are impacted disproportionately by environmental disturbances. The degree to which a community can remain unchanged under a disturbance is referred to as resistance1. However, the contributing ecological factors, which infer a community’s resistance are unknown. In this study, the impact of historical environmental stability on ecological phenomena and microbial community resistance to shocks was investigated. Three separate methanogenic bioreactor consortia, which were subjected to varying degrees of historical environmental stability, and displayed different levels of resistance to an organic loading rate (OLR) shock were sampled. Their community composition was assessed using high throughput sequencing of 16S rRNA genes and assembly based metagenomics. The effect environmental instability on ecological phenomena such as microbial community assembly, microbial niche breadth and the rare biosphere were assessed in the context of each reactor’s demonstrated resistance to an OLR shock. Additionally, metagenome assembled genomes were analysed for functional effects of prolonged stability/instability. The system which was subjected to more environmental instability experienced more temporal variation in community beta diversity and a proliferation of specialists, with more abundant two component regulatory systems. This community was more susceptible to deterministic community assembly and demonstrated a lower degree of resistance, indicating that microbial communities experiencing longer term environmental instability (e.g. variations in pH or temperature) are less able to resist a large disturbance.